Unexpected features in the optical vibrational spectra of δ-UO3 - Spano, Tyler L.; Shields, Ashley E.; Niedziela, Jennifer L.; Miskowiec, Andrew (Frontiers in Nuclear Engineering, 2022)
Uranium trioxide displays a complex chemical phase space, with at least six structurally distinct polymorphs accessible via different synthetic routes. Remarkably, despite its technological importance, full structural and electronic characterization of these polymorphs remains an open area of study. δ-UO3 in particular has attracted significant theoretical attention due to its high point group and space group symmetries, having U (VI) in octahedral coordination with polyhedra interconnected through corner-sharing to build a 3-D cubic lattice with space group symmetry Pm-3m and Z = 1. Critical experimental information, such as its optical vibrational spectra, are not known. Here, we study the Raman and infrared (IR) spectra of δ-UO3 together with the support of density functional theory (DFT) calculations for spectral interpretation. A symmetry analysis of the DFT-predicted phonon eigenmodes indicates that δ-UO3 should have two IR active modes and no Raman active modes. Experimental results, however, indicate significant Raman scattering from δ-UO3. We therefore propose four potential explanations for this apparent contradiction: a possible tetragonal distortion to the cubic cell, the existence of a surface impurity layer, vacancy scattering, and structural activation of Raman signal. We use powder X-ray diffraction and confocal Raman spectroscopy with depth profiling to investigate these possibilities and suggest future experiments to explore this phenomenon in more detail. Understanding the lattice dynamics of δ-UO3 is important for identification of technogenic U phases via Raman and infrared spectroscopy and our results indicate that the simple understanding of δ-UO3 as a high-symmetry cubic structure should be reconsidered.